2015
DOI: 10.1111/hsc.12230
|View full text |Cite
|
Sign up to set email alerts
|

Structure and process quality as predictors of satisfaction with elderly care

Abstract: What is known about this topic• Quality of care can be decomposed into three distinct but related components of structure, process and outcome.• Quality of caring relationships predicts satisfaction with care. What this paper adds• In a Swedish national survey, structural variables such as budget per elderly person and care personnel certification/training showed no relationships with the elderly person's evaluation of care in terms of satisfaction, while staffing and budget per capita AbstractThe structure ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 36 publications
4
58
3
Order By: Relevance
“…A study including data from the 2012 national eldercare survey showed no statistically significant association between users' experience of influence and care satisfaction in home help services. The authors suggest that the lack of significant association might be explained by the fact that the users receive care in their own home and, therefore, experience autonomy and influence (Kajonius & Kazemi ). The present study showed that many users did not believe it was really possible to influence care provision, and this belief might lead to strategies such as adaptation and trivialisation.…”
Section: Discussionmentioning
confidence: 99%
“…A study including data from the 2012 national eldercare survey showed no statistically significant association between users' experience of influence and care satisfaction in home help services. The authors suggest that the lack of significant association might be explained by the fact that the users receive care in their own home and, therefore, experience autonomy and influence (Kajonius & Kazemi ). The present study showed that many users did not believe it was really possible to influence care provision, and this belief might lead to strategies such as adaptation and trivialisation.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that it is not enough to provide information; the professionals also have to make a conscious effort to include the individual and his/ her informal caregiver or members of the team so that they are actively involved in the planning and decision-making process. To establish a true partnership, it is necessary to move away from didactic or paternalistic care provision [21]. Various professionals have to let go of their power and regard the individual as a competent partner involved in planning his or her own care.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, this previous research has convincingly demonstrated that satisfaction with care is mainly predicted by the experience of the care process at the interpersonal level (Kajonius and Kazemi, 2016c). Care process was tapped by ratings of how the older person perceived information sharing, respect from the care workers…”
Section: User-oriented Care and Satisfaction With Carementioning
confidence: 98%